An industrial systems design study on Calamba Water District - Dimaculangan, Mary Grace M.; Nilooban, Joan V.; Tardeo, Dacia Marisse P.; Villapando, Gina
This paper presents an Industrial Systems Design Study on Calamba Water District (CWD). It aims to document and improve the utility's current water supply system. Specifically, it seeks to measure and minimize CWD's non-revenue water, which was identified to be the utility's primary problem. Non-revenue water is the primary contributor to CWD's revenue losses. It also considerably increases operating costs and greatly impacts service quality. It ts not just a financial concern but also an environmental, sustainability, and even a health and safety issue. Most notably, it directly addresses attainment of the utility's mission and vision. However, non-revenue water has several components. Only the component relevant to Industrial Systems Design, which is real losses, was focused on this study. Opportunely, it is also the most significant component, comprising 97.45% of total non-revenue water. The Systems Design specialties of Systems Engineering were used to organize the documentation of CWD's current water supply system. These design specialties include Design for Reliability, Maintainability, Usability, Supportability, Serviceability, Producibility, Disposability, Sustainability, and Affordability. Design for Reliability was used to describe the system failure management, demand management, quality management, water pressure monitoring and regulation, water level monitoring, and hydrostatic testing procedures of CWD. Design for Maintainability was utilized to relate the water quality maintenance; pipeline and equipment maintenance; materials, equipment, and equipment parts maintenance; groundwater wells and spring maintenance; and facilities maintenance procedures. Design for Usability was employed to detail the training and operational procedures. Design for Supportability was used to define the equipment, materials, personnel, transportation, and facilities support systems. Design for Serviceability was utilized to record the duration of leak location and repair and equipment servicing. Designs for Producibility and Disposability were employed to illustrate the procedures for sourcing of water and disposal of blown-off water and scrap, respectively. Design for Sustainability was used to describe the surface water source development and groundwater well drilling projects. Lastly, Design for Affordability was utilized to account investments on improvement projects and decision-making policies for upkeep and replacement of major equipment. The DMAIC model of Lean Six Sigma was employed to structure the flow of the study. Define Phase components include objectives, scope and limitations, problem definition, goals, benefits, SIPOC Diagram, and Critical-to-Quality Tree. The problem was identified as a non-revenue water problem, particularly a real loss problem. Real losses, which manifest as leakages in the water supply system, account to 34.32% of total water produced. The SIPOC Diagram was created to delineate the boundaries of CWD's water supply system and to identify the involved suppliers, inputs, processes, outputs, and customers. The Critical-to-Quality Tree was constructed to show the drivers and metrics which would have to be tracked in order to ensure the reduction of real losses. Measure Phase elements include Performance Indicators, Check Sheet, and Pareto Chart. Performance indicators, which include non-revenue water by volume, real losses by volume, real losses per service connection per day, and infrastructure leakage index, were calculated to measure the efficiency and effectiveness of CWD's water supply system. Check Sheet was created to identify the leak source that contributes the highest frequency of leak occurrences. Lastly, the Pareto Chart was constructed to determine the leak source that produces the largest volume of real losses. Analyze Phase techniques are Five Whys Analysis, Tree Diagram, and Ishikawa Diagram. Five Whys Analysis was conducted to determine the true root causes of the real loss problem. The Tree Diagram was constructed to break down the problem into possible lower level problems. Lastly, the Ishikawa Diagram was created to schematically present the problem and the classified root causes. Improve Phase components include the Target Diagram, Current-State Value Stream Maps, Alternatives, Factor Rating Method, Cost Analysis, Implementation Roadmaps, Five S, Future-State Value Stream Maps, and Theory of Inventive Problem Solving (TRIZ). The Target Diagram was created to present the layers of objectives leading to the central target objective of reducing real losses to less than or equal to the ceiling benchmark of 22.45%. Current-State Value Stream Maps were also made to identify improvement opportunities in CWD's present leak control processes. Alternatives for reducing real losses were then researched. Factor Rating Method was subsequently employed to evaluate and recommend alternatives using cost, effectiveness, ease of implementation, ease of operation or performance, and ease of maintenance as the factors. Cost Analysis was conducted afterwards to calculate the implementation costs, life cycle costs, and costs per year of the recommended alternatives and the total implementation cost of the entire proposed real loss reduction program. Implementation Roadmaps were then created using the what, why, when, where, who, how, and how much format to summarize the action plans for the execution of the recommended alternatives. Five S principles were also outlined in order to serve as necessary supporting procedures for the implementation of the recommended alternatives. Future-State Value Stream Maps were then made to depict CWD's leak control processes upon implementation of the recommended alternatives and Five S suggestions. Theory of Inventive Problem Solving (TRIZ) was also employed to reduce the high frequency of leaks and large volume of real losses along service connections, which were previously identified to be the most significant contributor to frequency of leaks and volume of real losses. Control Phase tools include Process Decision Program Charts, Radar Chart, Control Plans, and Plan Do-Check-Act Cycle. Process Decision Program Charts were constructed to present countermeasures that can be taken to prevent potential problems in the proposed real loss reduction program from occurring in the first place and to mitigate the problems if they do occur. A Radar Chart was created to determine the ease of ensuring attainment of specified factors, which are the opposites of the potential problems identified in the Process Decision Program Charts. Control Plans were also made to monitor and supervise the recommended alternatives. Lastly, a Plan-Do-Check-Act Cycle was outlined to ensure the continuous improvement of the real loss reduction program.